Trampling, taphonomy, and experiments with lithic artifacts in the southeastern Baguales Range (Santa Cruz, Argentina) - Balirán, Catalina (2014)
This work assessess the impact of taphonomic processes on the surface lithic record of La Verdadera Argentina archaeological locality (Santa Cruz, Argentina). Different stages of weathering were observed on lithic artifacts´ surfaces, the edges consistently exhibiting less intense alteration, which may be the result of a reclamation process of the archaeological record or of animal trampling. At such, this project was designed to understand the potential effect of animal trampling on surface lithic artifacts. Toward this end, two experimental plots were established in La Verdadera Argentina. Results of these actualistic tests are used as a frame of reference for the taphonomic analysis of the surface artifact assemblage recovered along an archaeological survey transect (T9). Preliminary results indicate that the effects of taphonomic processes are registered very quickly. The hypothesis explaining the edge modifications observed in the local lithic record as a result of taphonomic processes cannot be discarded.